Inhibition of Streptococcus suis Adhesion and Biofilm Formation in Vitro by Water Extracts of Rhizoma Coptidis - Li, Yan-Hua; Zhou, Yong-Hui; Ren, Yong-Zhi; Xu, Chang-Geng; Liu, Xin; Liu, Bing; Chen, Jian-Qing; Ding, Wen-Ya; Zhao, Yu-Lin; Yang, Yan-Bei; Wang, Shuai; Liu, Di (Frontiers in Pharmacology, 2018)
Streptococcus suis (S. suis) is difficult to treat and responsible for various infections in humans and pigs. It can also form biofilms and induce persistent infections. Rhizoma Coptidis is a medicinal plant widely used in Traditional Chinese Medicine. Although the inhibitory effects of Rhizoma Coptidis on biofilm formation have been investigated in several studies, the ability of Rhizoma Coptidis to inhibit S. suis biofilm formation and the underlying mechanisms have not yet been reported. In this study, we showed that sub-minimal inhibitory concentrations (25 and 50 μg•mL-1) of water extracts of Rhizoma Coptidis (Coptis deltoidea C.Y.Cheng & P.K.Hsiao, obtained from Sichuan Province) were sufficient to inhibit biofilm formation, as shown in the tissue culture plate (TCP) method and scanning electron microscopy (SEM). Real-time PCR and iTRAQ were used to measure gene and protein expression in S. suis. Sub-minimum inhibitory concentrations (25 and 50 μg•mL-1) of Rhizoma Coptidis water extracts inhibited S. Suis adhesion significantly in an anti-adherence assay. Some genes, such as gapdh, sly and mrp, and proteins, such as antigen-like protein, CPS16V, and methyltransferase H, involved in adhesion were significantly modulated in cells treated with 50 μg•mL-1 of Rhizoma Coptidis water extracts compared to untreated cells. The results from this study suggest that compounds in Rhizoma Coptidis water extracts play an important role in inhibiting adhesion of S. suis cells and, therefore, biofilm formation.